Family involvement in behaviour management following acquired brain injury (ABI) in community settings: A systematic review. (June 2015) - Fisher, Alinka; Lennon, Sheila; Bellon, Michelle; Lawn, Sharon
Abstract Objectives: To examine family involvement in the management of behavioural problems following ABI in the community. Research design: Systematic literature review. Methods: Six electronic databases relevant to the field of brain injury were searched between 1980–2013. Citation indexes were used and references from articles hand searched for further literature. Studies that met the broad inclusion criteria were screened for relevance and articles selected for full-text review independently considered by two reviewers. Those found to be relevant were analysed using PEDro and McMasters critical appraisal tools. Results: Three hundred and three studies were identified after duplicates were removed and 56 were assessed for relevance, yielding 10 studies for review. Although the majority of studies were weak in design, five revealed significant findings supportive of family involvement in the management of behavioural problems following ABI, especially where interventions consisted of both educational components and individualized behavioural plans. Findings revealed no significant changes in family burden following behavioural interventions. Conclusions: There is limited research and lack of high evidence studies evaluating family involvement in behaviour management following ABI; therefore, no conclusions can be drawn regarding its efficacy. More research is needed, with larger sample sizes and more rigorous design, including proper comparison groups.